Ecuadorian private high school teachers` perceptions on ICT use in their EFL classes - Anitei, Anca María (2018)
Resumen: The purpose of the study, Ecuadorian private high school teachers` perceptions on ICT use in their EFL classes, is to discover the barriers and the characteristics that most influence teachers to use ICT in their EFL classrooms. The sample consisted of ten participants, five male and five female EFL teachers at private high schools in La Concordia, in the province of Santo Domingo de los Tsàchilas in Ecuador. This research used a quantitative and qualitative approach. The data was obtained by surveying and interviewing the chosen sample. The Likert scale analysis was used to determine barriers, influence on the teachers` characteristics, and differences by gender of each variable. The results showed that personal` characteristics of the teachers as traditional teaching experience, age, money and time are considered as barriers for the use of ICT. Differences were found by gender in the ICT application. Therefore, ICT training courses and schools technical equipment need to be increased for an optimal application of the ICT in Ecuadorian private high school EFL classes.